ANALISIS KUALITAS AUDITOR DAN FAKTOR YANG MEMPENGARUHINYA (Studi pada Auditor Pemerintah di BPKP Perwakilan Provinsi Lampung) - Hestin Ratna Wati; Victoria Ari Palma Akadiati (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2019)
The purpose of this study is to obtain empirical evidence to be known and analyzed about theinfluence of expertise, independence and ethics on audit quality in Government Auditors at BPKPRepresentatives of Lampung Province. Expertise is the ability of an auditor, the independence of mentalattitudes that can not be influenced by others, the ethics of a set of principles or values. This researchwas conducted at BPKP Lampung Province Representative.Sampling technique using non probability sampling with purposive sampling method, thesample used as much as 52 respondents. This research includes quantitative research. Using multiplelinear regression analysis. The results of this study show (1) Expertise affect the Quality Audit, (2)Independence affects Quality (3) Ethics does not affect the Quality Audit (4) Expertise, Independenceand Ethics affect the Quality Audit